AJARAN DASA DHARMA DALAM TRANSCENDENTAL MEDITATION DI SMA NEGERI BALI MANDARA SINGARAJA KABUPATEN BULELENG - Ni Wayan Murniti (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2022)
The Transcendental Mediation technique is an easy, natural and effortless process, which allows the consciousness to experience the realm of the mind from a subtler and more subtle level so that the thought process is transcended and awareness is directly connected to the source of the thought. Transcendental Meditation ethics in meditation practice include: 1) not related to place, as long as it is not disturbed, 2) not recommended in a sleeping position, 3) without contemplation, 4) without concentration, 5) without physical exercise, 6) no change in way life, such as dressing must be special, with Transcendental Mediation able to build harmonious relationships between school members. Transcendental Mediation is able to anticipate behavioral deviations. It has been proven that students who take part in Transcendental Mediation have good character. Transcendental Mediation is able to strengthen the religious foundation of students. Keywords: Transcendental Mediation